An unusual case of giant cardiac fibroelastoma mimicking left atrial myxoma in a patient presenting with syncope. Issue 3 (14th April 2012) - Khoueiry, Georges; Geha, Fady; Meghani, Mustafain; Abi Rafeh, Nidal; Azab, Basem; Torbey, Estelle; Asgarian, Kourosh T.; Sicat, Michael
Abstract Cardiac papillary fibroelastomas are the most common primary valvular tumors. Generally benign, they account only for about 10% of all primary cardiac neoplasms, can occur in normal or diseased hearts, and are associated strongly with open heart surgery and radiotherapy. They are, in most cases, incidental findings, but can be discovered after syncope. We report the case of an elderly female, who was referred for syncope and was found to have a large fibroelastoma at the mitral valve annulus, intermittently obstructing the left ventricular inflow tract, and mimicking the presentation of left atrial myxoma. This case illustrates another potential mechanism of syncope in patients with fibroelastomas. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound, 2013